2002
DOI: 10.1097/00003246-200209000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Use of plasma lactate to predict early mortality and adverse outcome after neonatal extracorporeal membrane oxygenation: A prospective cohort in early childhood*

Abstract: Fifteen (20%) neonates died before neonatal intensive care unit discharge (early deaths), with seven additional deaths before follow-up, which are included in the adverse survivors group. Among 49 early childhood survivors (22 +/- 7 months), 27 were disabled or delayed with Mental and Performance Developmental Indices of 70 +/- 21 and 72 +/- 22, respectively. Early deaths had higher plasma lactate levels and were more acidemic than adverse and normal survivors, who were not different from each other (p <.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 13 publications
2
34
1
Order By: Relevance
“…As for other critically ill children, lactate levels were predictive of mortality. 40 This study explored stages of cumulative risk factors and sought modifiable determinants of adverse outcome before, during, and after OHS. Overall, multivariate analyses explain 55% of the variance of outcome: 23% from the preoperative stage, 18% from the intraoperative stage, and 14% from the postoperative stages.…”
Section: Discussionmentioning
confidence: 99%
“…As for other critically ill children, lactate levels were predictive of mortality. 40 This study explored stages of cumulative risk factors and sought modifiable determinants of adverse outcome before, during, and after OHS. Overall, multivariate analyses explain 55% of the variance of outcome: 23% from the preoperative stage, 18% from the intraoperative stage, and 14% from the postoperative stages.…”
Section: Discussionmentioning
confidence: 99%
“…We think that this notion is most important in septic patients who have increased mortality. Rare combinations can be seen in daily clinical practice, and those combinations were also discussed in previous studies (Table 3) (6,9,13,(15)(16)(17)(18)(19). Kurt et al (15) indicated the presence of hypochloremic metabolic acidosis in 16% of acid-base disorders.…”
Section: Classification and Calculationsmentioning
confidence: 76%
“…However, these predictors identified are inconsistent among the previous studies. For instance, in a retrospective study of 49 neonates with severe hypoxemia requiring ECMO, the authors found that plasma lactate level higher than 25 mM was associated with higher mortality [15]. In adults, hyperlactatemia has been proven to be correlated well with mortality in ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ECMO support was performed as described previously [4,6,15]. In brief, our ECMO device (Medtronic Inc, Anaheim, CA) consisted of a centrifugal pump and a hollow-fiber microporous membrane oxygenator with an integrated heater.…”
Section: Ecmo Devicementioning
confidence: 99%